Facile patterning of microfluidic paper-based analytical devices (μPADs) by dispensing propylene glycol methyl ether acetate (PGMEA) - Xionghui Li; Xuanying Liang; Haonan Li; Jing Song; Kanghui Li; Muyang Zhang; Huiru Zhang; Zhuoting Han; Lok Ting Chu; Weijin Guo (Sensors and Actuators Reports)
Facile patterning of microfluidic paper-based analytical devices (μPADs) is highly intriguing for researchers using μPADs for point-of-care diagnostics. For the first time, this work introduces the use of propylene glycol methyl ether acetate (PGMEA) as a novel material to create barriers on μPADs, with the formation mechanism of these barriers investigated using scanning electron microscopy (SEM). A digitized and automated dispensing machine is employed for barrier creation, demonstrating the stability of the barriers in the presence of various organic and aqueous solvents including alkaline and acidic solutions, and surfactants. Additionally, we explore the possibility of rapid patterning of μPADs by hand drawing using PGMEA. The stability of the barriers created by PGMEA lays a solid foundation for various biomedical and chemical analyses. Moreover, we use this method to prepare μPADs for quantitative measurement of iodate content in saline solutions and blood typing analysis successfully, proving that μPADs prepared by this method have a significant potential for applications in point-of-care diagnostics.